Real-life behavioral and neural circuit markers of physical activity as a compensatory mechanism for social isolation - Anastasia Benedyk; Markus Reichert; Marco Giurgiu; Irina Timm; Iris Reinhard; Carina Nigg; Oksana Berhe; Alexander Moldavski; Christoph von der Goltz; Urs Braun; Ulrich Ebner‐Priemer; Andreas Meyer‐Lindenberg; et al. (2024)
Abstract Social isolation and loneliness pose major societal challenges accelerated by the coronavirus disease 2019 pandemic, especially for mental health. In this cohort study using accelerometry, electronic diaries and neuroimaging in a community-based sample of 317 young adults, we show that people felt affectively worse when lacking social contact, but less so when engaging in physical activity. This putative compensatory mechanism was present even at small physical activity doses and was pronounced in individuals with higher brain functional connectivity within the default mode network signaling risk for depression. Social-affective benefits of movement were higher in people showing exacerbated loneliness and were replicated throughout the pandemic. These findings extend the state of knowledge on the dynamic interplay of social contact and physical activity in daily life identifying an accessible protective strategy to mitigate the negative effects of social isolation, particularly among at-risk individuals, which comes with the potential to improve public health in the post-pandemic world.